A Bibliometric Analysis and Review of Global Trends on Collaborative Problem-Solving Skills at the Senior High School - Sri Suci Lesatari; Riska Dia Sapitri; Ryya Aulia Assiri (Current Educational Review, 2026)
Collaborative problem-solving (CPS) is recognized as a crucial 21st-century essential skill for students to collectively solve complex challenges. This study aims to review global trends in CPS research at the senior high school (SMA) level through a systematic literature review and bibliometric analysis over a decade from 2014 to 2024 (N = 2,247; exclusion criteria: non-English language studies published before 2014; inclusion criteria: meta-analysis articles included). Methods included a review of articles from international databases (e.g., PoP, Scopus, Web of Science) with bibliometric analysis using software such as VOSviewer to identify publication patterns, authors/institutions, and dominant keywords. The findings also showed that most studies concentrated on junior high school students, indicating a particular emphasis on this group, according to a systematic evaluation of 20 publications that met specific exclusion criteria. The findings of this study provide new insights into current trends, influential researchers, and novel approaches in assessing collaborative problem-solving skills that can inform future research and the development of collaborative problem-solving tools in education